Research Trends in the Development of an E-booklet on Butterfly Species Diversity in Kerandangan Nature Park to Improve Science Literacy of High School Students: A Systematic Review - Rita Alawiyah; Susilawati Susilawati; Gunawan Gunawan (Balai Publikasi Indonesia, 2025)
A Learning is an integral part of human life, enabling individuals to develop their potential and fulfil their needs through four pillars: learning to know, to work, to live together and to develop as a whole. Learning resources, which include everything that supports learning, play an important role in improving teaching effectiveness and enabling students to learn independently. This research examines the development of an Android-based butterfly diversity e-book as a learning resource to improve student learning outcomes and science literacy. The method used was descriptive analytical by analyzing 1,000 documents indexed in Google Scholar between 2015 and 2024. Results showed a significant upward trend in e-book-related publications after 2017, with some peaks in previous years. The data also shows that a large category of research is in the form of articles, with leading journals being the main source of publications. This research highlights the importance of developing innovative learning resources to support biodiversity learning, especially in the context of school teaching